Assessment of the psychological domain of the quality of life for infertile men - dallak, Abdul-Salam; Abdul-Salam, rabia (Iraqi National Journal of Nursing Specialties, 2005)
Abstract A descriptive correlation study which was utilizing an assessment approach, was carried out from November 19th, 2002 through April 30, 2004 in order to assess the psychosocial domain of the quality of life for the infertile men. A purposive sample of (200) men with infertility was selected from the High Institute for Embryo Research and Infertility Treatment and Alsamaraee Hospital in Baghdad city. A questionnaire was adoapted and developed of the World Health Organization quality of life scale for the purpose of the study. The questionnaire (WHOQOL) (1998) Reliability and validity of the questionnaire were determined through a pilot study. Data were collected through the use of the questionnaire, the application of the interview technique and review of the infertile men records. Data were analyzed through descriptive and the inferential data analysis approach. The findings of the study showed that the positive and negative feelings , thinking and self-esteem had impact on the quality of life for the infertile men . The findings of the study showed that the demographic characteristics of the infertile men of infertility duration, age of husband, first marriage, frequency sexual activity , marriage age had a highly significant relationship to the sub-domain of positive and negative feelings of the infertile quality of life. The findings of the study showed that there was a highly significant relationship between sexual impotence and the age of husband and the sub-domain of thinking of the quality of life . The findings of the study showed that quality of life had a strong relationship with the sub-domain of positive and negative feelings , thinking and self-esteem . The study recommended that an interventional and education oriented program can be designed , constructed and administered to the infertile men and their wives through which health and life related issues can be presented . Well – structured and highly – specialized infertility center can be established to provide infertility treatment and psychological and social counseling to all infertile men with reasonable cost.